2009
DOI: 10.1029/2009gl037629
|View full text |Cite
|
Sign up to set email alerts
|

Source regions of banded chorus

Abstract: ELF/VLF chorus emissions are very intense electromagnetic plasma waves that are naturally and spontaneously excited near the magnetic equatorial plane outside the plasmasphere during periods of magnetic disturbance. These emissions are believed to play an important role in the acceleration of 10 to 100 keV radiation belt electrons to MeV energies during the disturbed time periods. Spacecraft observations near the magnetic equatorial plane in the regions where chorus emissions are generated show that the chorus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 25 publications
4
65
0
Order By: Relevance
“…On the other hand, we did not find a gap at half the gyrofrequency in both Elements 1 and 2, which is evident in the observation. This difference implies that the mechanism of a gap at 0.5 Ω e0 is governed by the physical process that is not described by the spatially one-dimensional system treating purely parallel propagating electromagnetic waves, such as the nonlinear damping through Landau resonance Yagitani et al 2014) and/or properties of obliquely propagating whistler-mode waves (e.g., Bell et al 2009;Katoh 2014;Nunn and Omura 2015). Macúšová et al (2010) analyzed 13 events of whistlermode chorus observed by the Cluster spacecraft during different levels of geomagnetic activity and showed that the frequency sweep rate decreases with the decreasing background plasma density.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, we did not find a gap at half the gyrofrequency in both Elements 1 and 2, which is evident in the observation. This difference implies that the mechanism of a gap at 0.5 Ω e0 is governed by the physical process that is not described by the spatially one-dimensional system treating purely parallel propagating electromagnetic waves, such as the nonlinear damping through Landau resonance Yagitani et al 2014) and/or properties of obliquely propagating whistler-mode waves (e.g., Bell et al 2009;Katoh 2014;Nunn and Omura 2015). Macúšová et al (2010) analyzed 13 events of whistlermode chorus observed by the Cluster spacecraft during different levels of geomagnetic activity and showed that the frequency sweep rate decreases with the decreasing background plasma density.…”
Section: Resultsmentioning
confidence: 99%
“…The typical frequency range of chorus is from 0.2 to 0.8 Ω e0 , where Ω e0 is the electron gyrofrequency at the magnetic equator. Chorus are often classified into the lower band (0.2-0.5 Ω e0 ) and the upper band (0.5-0.8 Ω e0 ) because of the different propagation properties and characteristics appeared in the spectra accompanied with a distinct gap at half the gyrofrequency (e.g., Bell et al 2009). Since whistler-mode waves satisfy the cyclotron resonance condition with electrons in the wide range of kinetic energy and pitch angle, resonant scattering of energetic electrons in the magnetosphere has been extensively discussed by various approaches: by a diffusion code based on the quasi-linear theory (e.g., Thorne et al 2010), by a test-particle analysis (e.g., Albert 2001;Bortnik et al 2008), and by an analytic approach (e.g., Lakhina et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The propagation of whistler-mode waves along a field line of the density enhancement or density decrease has been studied for decades (e.g., Smith et al 1960). The propagation properties of whistler-mode chorus have also been discussed by theories (e.g., Bell et al 2009) and observations (e.g., Haque et al 2011) for the explanation of the spectral gap at half the gyrofrequency dividing chorus emissions into upper band and lower band. Figure 6 shows the radial distribution of the background cold electrons at the magnetic equator of the simulation system.…”
Section: Runs 2 and 3: Duct Propagation Of A Rising Tone Chorus Elementmentioning
confidence: 99%
“…The propagation properties of chorus are governed by the spatial distribution of ambient cold electrons controlling the dispersion relation of plasma waves. Previous studies have revealed conditions of trapping of whistler-mode waves within enhanced or depleted plasma density (Bell et al 2009). …”
mentioning
confidence: 99%
“…This is banded chorus and its existence has been known since 1969 but until recently there has been no satisfactory explanation of the phenomenon. Using WBD, Bell et al (2009) showed that banded chorus can be explained if chorus is excited in ducts of either enhanced or depleted cold plasma. The result was later verified by Haque et al (2011Haque et al ( , 2012.…”
Section: Betatron and Stochastic Accelerationmentioning
confidence: 99%